The Physical Modeling Analysis of Fate and Transport of Silver Nanoparticles Dispersed by Water Flow - Achmad Syafiuddin; Salmiati Salmiati; Mohamad Ali Fulazzaky; Dedy Dwi Prastyo; Raj Boopathy; Mu. Naushad (Journal of Chemistry)
The release of silver nanoparticles (AgNPs) from consumer products into an environment has become a central issue for many countries. Despite that the fate and behaviors of AgNPs incorporated into a wastewater have been investigated by building a model of wastewater treatment process, the transport and retention behaviors of AgNPs influenced by the water flow in a river must be understood. The physical model of simulated river to mimic a natural flow of river was proposed to investigate the behaviors of AgNP transport in the river. The results showed that the large amount of AgNPs deposited on the riverbed as Ag sediment with only 1.26% of AgNPs remained in the water flow. The elemental content of Ag freely dispersed across the riverbed increases from the upstream to downstream area of the simulated river. Verification of the spatial distribution of Ag dispersed along the water flow may contribute to a better understanding of the fate and transport of AgNPs in the aquatic environment.